Usefulness of Submental Ultrasonographic Evaluation for Dysphagia Patients - Lee, Yoon Soo (Ann Rehabil Med, 2016)
OBJECTIVE: To investigate the usefulness of ultrasonographic measurement of hyoid bone movement during swallowing. METHODS: Fifty-two patients who had swallowing dysfunction were enrolled in this study. When a patient swallowed 5 mL of water while maintaining an upright sitting position, hyoid bone movement during swallowing was measured with ultrasonography. Recorded images were analyzed to measure the maximum change in hyoid bone displacement. Mandible was used as reference point to calculate hyoid bone displacement. The farthest distance from resting position and the nearest distance during swallowing were measured and their differences were recorded. Participants also underwent videofluoroscopic swallowing study (VFSS). Based on penetration-aspiration scale (PAS), they were grouped to non-aspirators (PAS 1), penetrators (PAS 2–5), or aspirators (PAS 6–8). Measured hyoid bone displacements by submental ultrasonography were compared among groups. RESULTS: The mean hyoid bone displacement in non-aspirators group (n=21, 15.9±2.7 mm) was significantly (p<0.05) greater than that in penetrators group (n=20, 11.5±2.8 mm) or aspirators group (n=11, 8.0±1.0 mm). Hyoid bone displacement below 13.5 mm as a cutoff point for detecting penetration or aspiration had a sensitivity and specificity of 83.9% and 81.0%, respectively. CONCLUSION: Submental ultrasonographic evaluation was well correlated with PAS measured by VFSS. Therefore, submental ultrasonographic evaluation could be a useful screening tool for dysphagic patients.